Epizootological Monitoring and Age-Related Dynamics of Colibacteriosis and Pullorosis in Poultry - Muxammadiyev S.E; Murodov X.U; Akhmedov B.N (American Journal of Biology and Natural Sciences, 2026)
This study presents the results of an epizootological assessment of Pullorum dis-ease, Colibacillosis, and their mixed infections across different age groups of poul-try in two commercial farms of the Republic of Karakalpakstan. The investigation was conducted during the first quarter of 2026 at "Agro Biznes Qanliko’l" LLC (Qonliko’l district) and "Kungrad Golden Egg" LLC (Qo’ng’irot district). A total of 1,750 Lohmann Brown Classic layer chickens were included in epizootological monitoring: 1,000 birds from "Agro Biznes Qanliko’l" LLC and 750 birds from "Kungrad Golden Egg" LLC. The examined birds were distributed into four age groups: 1–9 weeks, 10–17 weeks, 18–25 weeks, and older than 26 weeks. For each age group, the overall morbidity rate and the individual occurrence of Pullorum disease, Colibacillosis, and mixed infections were evaluated separately. The overall morbidity rate was 10.7% at "Agro Biznes Qanliko’l" LLC and 8.9% at "Kungrad Golden Egg" LLC. In both farms, the highest morbidity was recorded in 1–9-week-old chicks, reaching 15.2% and 12.0%, respectively, with a progressive decline in older age groups, converging to 6.0% in birds older than 26 weeks. Mixed infec-tions constituted the dominant disease form in younger birds at "Agro Biznes Qanliko’l" LLC (4.8%), while Pullorum disease alone was more prevalent at "Kungrad Golden Egg" LLC (4.4%). Chi-square analysis confirmed a statistically significant association between age group and morbidity at "Agro Biznes Qanliko’l" LLC (χ² = 13.47, df = 3, p = 0.004), while no statistically significant in-ter-farm difference was identified (χ² = 1.494, p = 0.222). Binary logistic regression identified age as an independent predictor of morbidity: compared with 1–9-week-old chicks, birds older than 26 weeks demonstrated markedly reduced odds of dis-ease occurrence (OR = 0.395; 95% CI: 0.249–0.625; p < 0.001). The findings pro-vide a scientific basis for identifying age-related risk groups, improving epizooto-logical monitoring, and developing targeted veterinary-sanitary preventive measures based on age-related susceptibility in poultry farms of the Republic of Karakalpakstan.